Performance study of block cipher and stream cipher in real-time application using embedded system - Mohd Alif, Abd Ghani; Mohd Izril, Ishak; Rohani, S. M. Farook; Rusnida, Romli; Ong, Bi Lynn (Universiti Malaysia Pahang (UMP), 2010)
MUCEET 2009 is organized by Malaysian Technical Universities Network (MTUN) comprising of Universiti Malaysia Perlis (UniMAP), Universiti Tun Hussein Onn (UTHM), Universiti Teknikal Melaka (UTeM) and Universiti Malaysia Pahang (UMP), 20th - 22nd June 2009 at M. S. Garden Hotel, Kuantan, Pahang.